THE EFFECTS OF FIRM SIZE AND DEBT TO EQUITY RATIO ON TAX AVOIDANCE (International Journal of Psychosocial Rehabilitation, 2020)
Background Medina and Schneider (2018) found that underground economy activities in Indonesia throughout the 1991-2015 range reached an average of 24.11 percent of GDP. A gap of 24.11 percent can be interpreted that the level of taxpayer compliance in Indonesia is still low. This underground economy practice will cause the tax ratio not to be in line with GDP growth. According to Erly Suandy (2002: 7) Taxpayers try to pay taxes as small as possible because by paying taxes means reducing the economic capacity of the company. The high debt tax that must be paid by the company makes the company try to minimize the large debt tax burden (Jessica and Toly, 2014). The effort made by taxpayers to escape from paying taxes is a business called resistance to taxes. Tax resistance is often manifested in the form of passive resistance and active resistance. One of the active resistance often carried out by corporate and corporate taxpayers is tax evasion (Thomas Sumarsan 2013: 8). The phenomenon related to tax avoidance in Indonesia in 2017, according to the General Secretary of Forum Indonesia untuk Transparansi Anggaran Indonesian (FITRA) Adhitya Himawan (2017), that tax evasion is a serious problem in Indonesia. Every year there is Rp. 110 trillion which is a tax avoidance figure. most are business entities, around 80 percent and the rest are individual taxpayers. One of the factors that influence the occurrence of tax avoidance is firm size. According to Hormati (2009: 291) firm size is a scale or value where the company can be classified as small based on total assets, log size, stock value, and so forth. The greater the total assets, the greater the firm size. Other indications of tax avoidance companies can be seen from the policies taken by the company. Leverage can increase the number of loans that cause additional costs on demand for interest or interest. corporate tax, so the tax burden that must be paid by the company will decrease (Saudi, 2018)..